1996
DOI: 10.1523/jneurosci.16-13-04186.1996
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Retinal Ganglion Cells from Natural and Axotomy-Induced Cell Death in Neonatal Transgenic Mice Overexpressing bcl-2

Abstract: Approximately half of the retinal ganglion cells (RGCs) present in the rodent retina at birth normally die during early development. Overexpression of the proto-oncogene bcl-2 recently has been shown to rescue some neuronal populations from natural cell death and from degeneration induced by axotomy of nerves within the peripheral nervous system. Here we study in vivo the role of the overexpression of bcl-2 in the natural cell death of RGCs and in the degenerative process induced in these cells by transection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
93
2

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(108 citation statements)
references
References 46 publications
13
93
2
Order By: Relevance
“…We have shown previously that overexpression of bcl-2 in Grid2 Lc/ϩ olivary neurons will rescue most of the olivary neurons from target-related cell death (Zanjani et al, 1998b). This result is consistent with previous studies showing in vitro rescue of neurons from trophic factor withdrawal (Garcia et al, 1992;Allsopp et al, 1993;Batistatou et al, 1993) and in vivo rescue of neurons from axotomy or ischemia by bcl-2 overexpression Martinou et al, 1994;Farlie et al, 1995;Bonfanti et al, 1996;De Bilbao and Dubois-Dauphin, 1996) or deletion of Bax expression (Deckwerth et al, 1996;White et al, 1998).…”
Section: Granule Cell Survival and Olivary Neuron Deathsupporting
confidence: 91%
“…We have shown previously that overexpression of bcl-2 in Grid2 Lc/ϩ olivary neurons will rescue most of the olivary neurons from target-related cell death (Zanjani et al, 1998b). This result is consistent with previous studies showing in vitro rescue of neurons from trophic factor withdrawal (Garcia et al, 1992;Allsopp et al, 1993;Batistatou et al, 1993) and in vivo rescue of neurons from axotomy or ischemia by bcl-2 overexpression Martinou et al, 1994;Farlie et al, 1995;Bonfanti et al, 1996;De Bilbao and Dubois-Dauphin, 1996) or deletion of Bax expression (Deckwerth et al, 1996;White et al, 1998).…”
Section: Granule Cell Survival and Olivary Neuron Deathsupporting
confidence: 91%
“…For example, overexpression of a bcl-2 transgene increases RGC survival after axotomy in neonatal mice (27) and maintains the longterm survival (29) and normal electrophysiological response (57) of axotomized RGCs in adult mice. Bcl-2 overexpression also promotes the RGC axons to regrow (58).…”
Section: Discussionmentioning
confidence: 99%
“…In Bcl-2 transgenic mice, Bcl-2 overexpression blocks naturally occurring neuronal death (26,27) and reduces axotomyinduced (27)(28)(29)(30), ischemia-induced (26), and chemically induced (31) neuronal death. Similarly, Bcl-XL overexpression inhibits axotomy-induced (32) and ischemia-induced apoptosis (32,33) in transgenic mice.…”
mentioning
confidence: 99%
“…Overexpression of the antiapoptotic gene bcl-2, shown to reduce developmental apoptosis of neurons including ganglion cells, 20 protects ganglion cells from apoptosis following pathologic in vivo axotomy. 21 We have recently shown that deficiency of Bax and Bak blocks normal developmental apoptosis of rod photoreceptors, 3 and overexpression of bcl-x L , an antiapoptotic bcl-2 family member, blocks developmental lead exposure induced photoreceptor cell death. 22 Bcl-2 family members may similarly be involved in additional photoreceptor degenerations.…”
Section: Introductionmentioning
confidence: 99%